2009
DOI: 10.1038/jp.2009.110
|View full text |Cite
|
Sign up to set email alerts
|

Does skin cleansing with chlorhexidine affect skin condition, temperature and colonization in hospitalized preterm low birth weight infants?: a randomized clinical trial

Abstract: Objective: To examine if single skin cleansing with 0.25% chlorhexidine affects skin condition, temperature and bacterial colonization in stable preterm (28-36 weeks gestational age) low birth weight (1001-2000 g) infants admitted in a health facility.Methods: Eligible infants were randomized within 3 h of birth into the following three groups: chlorhexidine, normal saline or no skin cleansing. Infants in the first two groups were wiped once with baby wipes containing either 0.25% chlorhexidine or saline. Skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
3
33
1
1
Order By: Relevance
“…16 Among the studies which reported on the effect of chlorhexidine on bacterial skin colonization, the study by Jeeva Sankar et al in 2009 reported the colonization rates with Gram-negative pathogens were comparable between the 0.25 % aqueous chlorhexidine cleansing, normal saline cleansing and no cleansing groups at both 24 and 72h after the single cleansing. 10 This was similar to present study results.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…16 Among the studies which reported on the effect of chlorhexidine on bacterial skin colonization, the study by Jeeva Sankar et al in 2009 reported the colonization rates with Gram-negative pathogens were comparable between the 0.25 % aqueous chlorhexidine cleansing, normal saline cleansing and no cleansing groups at both 24 and 72h after the single cleansing. 10 This was similar to present study results.…”
Section: Discussionsupporting
confidence: 83%
“…9,10,17,18 A similar study was done in Bangladesh (2007) attempting to study the extended cleansing effects of 0.25% chlorhexidine. Their skin colonization rates seem comparable to be to us.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 High-risk term and preterm infants are at an increased risk of infection due to their illness, and in preterm infants due to immature skin and immune systems. 19,20 Caregiving equipment not only comes in contact with infants, but items like electrocardiogram (EKG) leads, monitoring probes, adhesive dressings, and chemical burns that can damage the epithelium can also lead to increased risk of microbial invasion. 20 Over the past two decades several NICU outbreaks of Pseudomonas aeruginosa and Klebsiella pneumoniae neonatal infections were linked to healthcare providers and caregiving activities, 21-24 but they fail to inform us about the development of the infant’s microbiome.…”
mentioning
confidence: 99%
“…23 In premature infants, bathing with chlorhexidine gluconate reduced skin colonization only transiently. 24 Concerns have also been raised about the potentially negative effect it may have on normal skin colonization.…”
Section: First Bathmentioning
confidence: 99%